2019
DOI: 10.1016/j.heliyon.2019.e01247
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for processing climate missing databases applied to daily rainfall data in Soummam watershed, Algeria

Abstract: Missing data is a very frequent problem in climatology, it influences on the quality of results that will afford in hydrological studies, as well as water resources management. This paper proposes a new imputation algorithm, based on the optimization of some regression methods, which are hot deck, k-nearest-neighbors imputation, weighted k-nearest-neighbors imputation, multiple imputation, linear regression and simple average method. The choice of these methods was justified by qualitative and quantitative sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 32 publications
0
32
0
1
Order By: Relevance
“…The choice of the methods is based on percentage of data missed and choice of neighboring stations. When the amount of the data filled are less than 5%, linear regression can be used by identifying the relationship between the observed data of neighboring stations and that of reference station (Aieb et al, 2019). In this study, the recorded data had missed values randomly and the percentage of the missing data were less than 4%.…”
Section: Observed Datamentioning
confidence: 92%
“…The choice of the methods is based on percentage of data missed and choice of neighboring stations. When the amount of the data filled are less than 5%, linear regression can be used by identifying the relationship between the observed data of neighboring stations and that of reference station (Aieb et al, 2019). In this study, the recorded data had missed values randomly and the percentage of the missing data were less than 4%.…”
Section: Observed Datamentioning
confidence: 92%
“…It is possible to verify that the models used managed, in a certain (2021) 3:687 | https://doi.org/10.1007/s42452-021-04679-1 way, to capture the behavior of the series, since the margin of error was low and variable depending on the year (Table 4). This study may have ramifications such as those carried out by Barrios,Trincado,and Garreaud [74] in monthly precipitation records and Aieb et al [75] to daily rainfall considering data imputation methods such as an artificial neural network (ANN), multiple linear regression (MLR), among others.…”
Section: Discussionmentioning
confidence: 99%
“…The Table 1 showed that the missing rainfall data had an interval range of (1.1%, 14.2%), whereas the temperature values are less frequent, which had an interval range of (0.2%, 4.1%). Hence, the missing data have been processed by using the new approach proposed in our former work to get a continuous and reliable time series (Aieb et al, 2019).…”
Section: Methodsmentioning
confidence: 99%